Highly localized divergence within supergenes in Atlantic cod (Gadus morhua) within the Gulf of Maine. - Barney, Bryan T.; Munkholm, Christiane.; Walt, David R.; Palumbi, Stephen R. (2017)
Background: Atlantic cod (Gadus morhua), is known to vary genetically across the North Atlantic, Greenland, and Newfoundland. This genetic variation occurs both spatially and temporally through decades of heavy fishing, and is concentrated in three linkage disequilibrium blocks, previously defined by pedigreed linkage mapping analysis. Variation within these genomic regions is correlated with both seawater temperature and behavioral ecotype. The full extent and nature of these linkage groups is important information for interpreting cod genetic structure as a tool for future fisheries management.; Keywords: Atlantic cod, Gadus morhua, Linkage disequilibrium, Linkage map, Genomic divergence, Supergene, Gulf of Maine.; Springer Open.